HUBUNGAN ANTARA PERSEPSI SISWA TERHADAP BIMBINGAN KONSELING DENGAN INTENSITAS PEMANFATAN LAYANAN KONSELING INDIVIDUAL DI KELAS VIII SMPN 9 PALANGKA RAYA - Akbar, Muhammad Hariadi; Sangalang, Merson U.; Pan Pangestie, Esty (Jurnal Bimbingan dan Konseling Pandohop, 2021)
Perception is a subjective process of processing how humans can judge an object. Many things affect perception, including existing stimuli, environmental factors, observations and experiences. Behavior appears based on the perceptions of each individual. The phenomenon that occurs at SMPN 9 Palangka Raya is that students are reluctant to consult voluntarily with counseling teachers, which means that students only come to the counseling teacher when called because they have committed a violation. This study aims to obtain an overview of the relationship between student perceptions and counseling guidance services in Class VIII. SMPN 9 Palangka Raya. The population of this study were students of SMPN 9 Palangka Raya which consisted of 3 (three) classes VIII-A VIII-B VIII-C, totaling 72 students. While the research sample using total sampling, which is to draw all the population as a sample. Data collection techniques in research using a draw and interviews. Furthermore, the results of the questionnaire data were analyzed using the product moment calculation technique, the r value was obtained, namely 0.841. Furthermore, the calculated r value is consulted with the product moment table r with N = 72 and the level of truth is 1%, namely, 0.368. The results obtained were, 4,841> 0.368. The conclusion from the above analysis is that there is a significant relationship between students' perceptions of BK services at SMPN 9 Palangka Raya.